Eksistensi Generasi Milenial Dalam Menumbuhkan Entrepreneur Di Era Kompetitif - Sewang Sewang (Universitas 45 Surabaya, 2023)
The role of the millennial generation today has a very significant impact in advancing the nation. They have a broad mindset that allows them to act as innovators and pioneers, not just following existing trends. Millennials have the potential to create new changes in society. However, creating young entrepreneurs is not easy. An individual with an entrepreneurial spirit must have strong self-belief, be future-oriented, as well as creativity and innovation. It is important to remember that an entrepreneur is not only focused on personal success, but also has a social responsibility to encourage the advancement of others. Helping others succeed will contribute to an increase in the number of entrepreneurs in Indonesia, which in turn will accelerate the development process in the country. Therefore, the millennial generation needs to gain understanding and continuous mentoring to develop their entrepreneurial spirit. The existence of entrepreneurs is essential for economic growth in Indonesia.